2021
DOI: 10.52711/0975-4385.2021.00029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Ulcer activity of Tephrosia purpurea Linn Pers Leaf Extract in Wistar Rats

Abstract: India is known for its traditional medicinal system – Ayurveda, Siddha and Unani. There are several references in our ancient literature about the miraculous curing properties of the plant-based drugs. “Rig Veda and Atharva veda” seems to be the earliest record of use of plant in the medicine. A stomach ulcer involves an erosion in a person’s gastrointestinal tract. ‘Peptic’ is derived from Greek word “Peptikos” who’s meaning is related to digestion. Peptic ulcer occurs in the part of the gastrointestinal trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was found that the extract decreased colonic malondialdehyde (MDA) and increased colonic glutathione (GSH), glutathione peroxidase (GPx), and catalase (CAT) activities (75) . The anti-inflammatory effect of leaf ethanolic extract was also confirmed by its ability to decrease carrageenan-induced edema in rat paws by about 47.16% (76) . One of the most interesting outcomes of the anti-inflammatory properties of A. squamosa is the anti-psoriatic effect of seed oil.…”
Section: Anti-inflammatory Activitymentioning
confidence: 76%
“…It was found that the extract decreased colonic malondialdehyde (MDA) and increased colonic glutathione (GSH), glutathione peroxidase (GPx), and catalase (CAT) activities (75) . The anti-inflammatory effect of leaf ethanolic extract was also confirmed by its ability to decrease carrageenan-induced edema in rat paws by about 47.16% (76) . One of the most interesting outcomes of the anti-inflammatory properties of A. squamosa is the anti-psoriatic effect of seed oil.…”
Section: Anti-inflammatory Activitymentioning
confidence: 76%